Impact of Direct-Acting Antiviral Treatments on Insulin Resistance Reversal in Chronic Hepatitis C Patients - Zubair, Muhammad; Pasha, Najaf Ali; Khan, Hashmatullah; Rafique, Khawar; Rao, Muhammad Ahmad; Sadiq, Zohaib (Biological and Clinical Sciences Research Journal, 2025)
Hepatitis C virus (HCV) infection is linked to metabolic complications, including insulin resistance (IR), which can increase the risk of type 2 diabetes mellitus (T2DM), liver fibrosis progression, and cardiovascular diseases. Direct-acting antiviral (DAA) therapy has revolutionized HCV treatment, leading to sustained virologic response (SVR), but its impact on insulin resistance remains under investigation, particularly in HCV genotype three patients. Objective: To assess the effect of direct active antiviral treatment on insulin resistance reversal in hepatitis C genotype three patients achieving sustained virologic response. Methodology: A case-control study was conducted in the Medicine Department of Mayo Hospital from Aug 2024 to November 2024. A total of 100 hepatitis C genotype three patients with advanced liver fibrosis being considered for treatment with DAAs were selected for study. Patients were divided into cases, i.e., 50 patients treated with DAAs, and the control group, i.e., 50 patients left untreated. Blood plasma and serum samples were collected before treatment initiation, after treatment completion, and at 3-month follow-up to check insulin and glucose levels in cases. In the control group, patients were assessed at the start of the study (Time 0) and the 3-month follow-up. Results: Insulin resistance at t0 was 56% vs 58%. HCV clearance was achieved in all patients, and 48 (96%) achieved SVR. Hepatic stiffness in cases was 19.12 ± 9.1 kPa before the start of treatment and 18.84 ± 7.3 after treatment and significantly lower at follow-up (12.45 ± 8.0) (p<0.001). Liver stiffness and steatosis did not change significantly in the control group during the study period. Fasting glucose was 95.59 ± 10.10 mg/dl at baseline, showing significant improvements at follow-up (83.17 ± 12.36). The control group showed no considerable glucose, insulin, or IR variations. A significant association between HOMA-IR and HCV-RNA levels was noted at baseline and a trend was found for hepatic stiffness (p=0.069) and BMI (p=0.060).Conclusion: HCV clearance through direct-acting anti-viral treatment improves or reverses insulin resistance in Hepatitis C genotype III patients, reducing the risk of diabetes mellitus, advanced liver fibrosis, metabolic syndrome, and cardiovascular events.